ANALISIS SIFAT MAGNETIK DAN STRUKTUR PARTIKEL PASIR BESI PANTAI ARTA PARIAMAN SUMATERA BARAT MENGGUNAKAN BALL MILLING - Wita Yulia; Erwin Erwin (Universitas Riau, 2019)
Analisys of magnetic properties and structure of particles of iron sand of Arta, Pariaman beach West Sumatra. Has been conducted the iron sand samples were dried, then the iron sand separation process was carried out using Iron Sand Separator (ISS). Next, the sample was milled for 30, 60 and 90 hours. The separation between magnetic particles and non magnetic particles was done using Neodymium Iron Boron (NdFeB) magnet. Magnetic induction measurements were carried out using Pasco PS-2162 Magnetic Probe which measured the total magnetic induction of solenoid (solenoid with core sample and milled sample(consentrate II)) as a function of electric current of 1-8 A for a fixed distance of 1 mm. Identification of the content of elements contained in iron sand before and after processing with Ball Milling for 90 hours was carried out using X-Ray Fluorescence (XRF). The phase of magnetic particles processed by Ball Milling was determined using X-Ray Diffraction (XRD). The calculation results show that the magnetic susceptibility of the sample increases with increasing Ball Milling time, from (69426,19 × 10-5 – 80332,13 × 10-5). These values are in the interval 220 - 380.000 × 10-5of the Ilmenite mineral. The magnetite phase appears more than the maghemite phase and the hematite phase after Ball Milling for 90 hours. The particle size of magnetik particle decreases as milling time increase, this trend is confirmed by the result of XRD.